Brain Measures of Toddlers’ Shape Recognition Predict Language and Cognitive Skills at 6–7 Years - Borgström, Kristina; Torkildsen, Janne von Koss; Sahlén, Birgitta; Lindgren, Magnus (Frontiers in Psychology, 2019)
While a number of studies have found that an improvement in object shape recognition is associated with language growth in infants and toddlers, no published studies have investigated the longitudinal relation between early shape recognition and language abilities in later childhood. An electrophysiological measure of semantic processing (the N400) was used to assess shape recognition and general object recognition in a naming context in 20-month-olds. The measures of shape recognition strongly predicted language and cognitive abilities at 6-7 years even after controlling for toddler vocabulary size. The electrophysiological measures of general object recognition were not related to future language or cognitive abilities. These results suggest that early shape recognition abilities may play a role in language acquisition and influence even long-term language outcomes.